MAPPING OF LEADING ECONOMIC SECTORS IN LAMPUNG PROVINCE 2018-2022 - Ramadian.M, Vivi Adelia; Rahma, Hanny Nur; Maulana, Arswenda Putra; Kartiasih, Fitri (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
A country or region certainly has the potential of each that is different. This potential has a large contribution to the economy in the region. Assessment of economic conditions is needed to determine the right strategy for the development of potential economic sectors so as to strengthen regional economic growth. Lampung Province needs to make improvements in the economic sector because it has a low growth rate and has a lower growth rate than Indonesia in the last two years. The purpose of this study is to show the leading sectors in the economy in the Province to be prioritized and given more attention in assisting regional development and to map the condition of each sector at the district/city level in Lampung Province. From the identification of leading sectors using Location Quotient, Shift Share and Klassen Typology, the Agriculture, Forestry and Fishery sectors; Water Procurement, Waste Management, Waste and Recycling; Construction; Wholesale and Retail Trade; Car and Motorcycle Repair; Transportation and Warehousing; Information and Communication; Real Estate is a leading sector in Lampung Province. Meanwhile, the mapping of sector conditions resulted in 5 sectors that experienced changes in the distribution of districts/cities in Lampung Province. In general, the leading sector in 2018 will be the agricultural sector, while in 2022 it will be the agricultural and processing sector.